(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Aromatic dicarboxylic acids are aromatic compounds with two carboxyl groups, often located on a benzene ring. Their properties and transformations are unique, and their complete correction and reactions are discussed.